If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) + -1(x + 2) = (x + 2)(x + -4) Reorder the terms: 2(-4 + x) + -1(x + 2) = (x + 2)(x + -4) (-4 * 2 + x * 2) + -1(x + 2) = (x + 2)(x + -4) (-8 + 2x) + -1(x + 2) = (x + 2)(x + -4) Reorder the terms: -8 + 2x + -1(2 + x) = (x + 2)(x + -4) -8 + 2x + (2 * -1 + x * -1) = (x + 2)(x + -4) -8 + 2x + (-2 + -1x) = (x + 2)(x + -4) Reorder the terms: -8 + -2 + 2x + -1x = (x + 2)(x + -4) Combine like terms: -8 + -2 = -10 -10 + 2x + -1x = (x + 2)(x + -4) Combine like terms: 2x + -1x = 1x -10 + 1x = (x + 2)(x + -4) Reorder the terms: -10 + 1x = (2 + x)(x + -4) Reorder the terms: -10 + 1x = (2 + x)(-4 + x) Multiply (2 + x) * (-4 + x) -10 + 1x = (2(-4 + x) + x(-4 + x)) -10 + 1x = ((-4 * 2 + x * 2) + x(-4 + x)) -10 + 1x = ((-8 + 2x) + x(-4 + x)) -10 + 1x = (-8 + 2x + (-4 * x + x * x)) -10 + 1x = (-8 + 2x + (-4x + x2)) Combine like terms: 2x + -4x = -2x -10 + 1x = (-8 + -2x + x2) Solving -10 + 1x = -8 + -2x + x2 Solving for variable 'x'. Reorder the terms: -10 + 8 + 1x + 2x + -1x2 = -8 + -2x + x2 + 8 + 2x + -1x2 Combine like terms: -10 + 8 = -2 -2 + 1x + 2x + -1x2 = -8 + -2x + x2 + 8 + 2x + -1x2 Combine like terms: 1x + 2x = 3x -2 + 3x + -1x2 = -8 + -2x + x2 + 8 + 2x + -1x2 Reorder the terms: -2 + 3x + -1x2 = -8 + 8 + -2x + 2x + x2 + -1x2 Combine like terms: -8 + 8 = 0 -2 + 3x + -1x2 = 0 + -2x + 2x + x2 + -1x2 -2 + 3x + -1x2 = -2x + 2x + x2 + -1x2 Combine like terms: -2x + 2x = 0 -2 + 3x + -1x2 = 0 + x2 + -1x2 -2 + 3x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -2 + 3x + -1x2 = 0 Factor a trinomial. (-2 + x)(1 + -1x) = 0Subproblem 1
Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {2, 1}
| 6y=23+7 | | 4x+15=2x | | 2+3z= | | -3(5n+6)=-93 | | 29y=7(4y-3) | | -126=6(8x+3) | | x=7+4(y-3) | | -8a-3a=-22 | | 4n-3n=-7 | | 14+10A=44 | | -n+8n=21 | | (3x-1)(2x+4)=0 | | 33-7n=8(1-4n) | | 6x^2+1=12 | | -37-52=11z-85 | | 1-3v+1=2 | | x.2-8x-20=0 | | -3x-x=4 | | 21+7x=7(6x-7) | | 6m-7=8m+19 | | 3(x+4)=-2(x-7)-15 | | 7x=8x-6 | | 14-2x=2(7-x) | | 45x-36y=180 | | -37=-1+3(3n-3) | | x^3+x^2-56x=0 | | x^2+4x+17= | | -36=-1+3(3n-3) | | 5x+2=x+(2x-10) | | .6u+2=6 | | Y=16+.4(62) | | 2x^2+2x=-8x-12 |